The Influence of the Existence of an Oversight Committee and the Extent of Voluntary Disclosure on Stock Prices In Indonesia - Ari Pradhanawati; Dinalestari Purbawati; Agung Budiatmo (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
This study consists of two test models. The first model investigates the impact betweenthe existence of anoversight committee on the extent of voluntary disclosure. The second test model investigates the impact betweenthe extent of voluntary disclosure on stock price.The data was collected from the annual reports non-financial companies listed on the Indonesian Stock Exchange (BEI) the period 2012, 2013 and 2014. Analysis tools used in the first test model is a multiple regression and a second test using simple regression model is also performed. The results of analyses show that only the existence of the risk management committee has a significant positive effect on the extent of voluntary disclosure. Then, the extent of voluntary disclosure has a significant positive effect on stock prices.